2017
DOI: 10.3892/or.2017.5600
|View full text |Cite
|
Sign up to set email alerts
|

A nine-miRNA signature as a potential diagnostic marker for breast carcinoma: An integrated study of 1,110 cases

Abstract: Growing evidence indicates that microRNAs (miRNAs) play critical roles in the initiation and progression of breast carcinoma (BC) and are promising diagnostic biomarkers. In the present study, we aimed to identify a multi-marker miRNA pool with high diagnostic performance for BC. We collected miRNA expression profiles of BC samples and normal breast tissues from The Cancer Genome Atlas (TCGA) and screened differentially expressed miRNAs by conducting two‑sample t-tests and by calculating log2 fold-change (log2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…In recent study, seven microRNAs (miR-21, miR-96, miR-141, miR-182, miR-183, miR-200a and miR-429) were upregulated and two microRNAs (miR-139 and miR-145) were downregulated in human BC. 24 A systematic review showed that two candidate microRNAs (miR-21 and miR-210) were upregulated and six microRNAs (miR-99a, miR-139-5p, miR-145, miR-195, miR-205 and miR-497) were downregulated in BC tissues comparing with normal tissues. 25 Many research have showed that miR-1247-5p was downregulated in cancer tissues, and it act as a tumour inhibition factor.…”
Section: Discussionmentioning
confidence: 99%
“…In recent study, seven microRNAs (miR-21, miR-96, miR-141, miR-182, miR-183, miR-200a and miR-429) were upregulated and two microRNAs (miR-139 and miR-145) were downregulated in human BC. 24 A systematic review showed that two candidate microRNAs (miR-21 and miR-210) were upregulated and six microRNAs (miR-99a, miR-139-5p, miR-145, miR-195, miR-205 and miR-497) were downregulated in BC tissues comparing with normal tissues. 25 Many research have showed that miR-1247-5p was downregulated in cancer tissues, and it act as a tumour inhibition factor.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important in cancer, a thoroughly heterogenous disease, where a multimarker approach would be preferable. To this extent, a nine-miRNA multimarker panel for breast carcinoma has already been shown to significantly improve the reliability of breast cancer diagnosis [89].…”
Section: The Potential Of Mirnas As Biomarkersmentioning
confidence: 99%
“…As for the classical biomarkers, the combination of multiple miRNAs or the combination of a miRNA with protein biomarkers, may increase the sensitivity and specificity of diagnosis and prediction of the studied condition. In supporting this notion, Xiong and co-workers have recently identified a panel of nine miRNAs allowing the early detection of breast cancer with a high diagnostic accuracy with a sensitivity of 98.70% and a specificity of 98.90% [45]. Seeliger et al identified a set of nine miRNAs (hsa-miR-21, hsa-miR-23a, hsa-miR-24, hsa-miR-93, hsa-miR-100, hsa-miR-122a, hsa-miR-124a, hsa-miR-125b, and hsa-miR-148a) significantly upregulated in serum and six miRNAs (hsa-miR-21, hsa-miR-23a, hsa-miR-24, hsa-miR-25, hsa-miR-100, and hsa-miR-125b) significantly upregulated in bone tissues of patients with osteoporosis fractures compared to patients with non-osteoporotic fractures, with five miRNAs upregulated in both serum and bone tissues.…”
Section: Overview On Present or Future Clinical Applications Of Mirnasmentioning
confidence: 90%